The Effect of Behaviour Intention on Academic Performance of Vocational Students in Blended Learning: A Case Study in Information Technology Courses - Sancoko, Sancoko; Hawadi, Lydia Freyani; Yola, Lin; Kesa, Deni Danial (Jurnal Pendidikan Progresif, 2025)
There are three type of learning models, one of which is blended learning. Blended learning is learning that combines face-to-face instruction with e-learning. Program Vokasi Universitas Indonesia encourages lecturers to implement this model to enhance the quality of vocational students. Universitas Indonesia support for blended learning is shown through the Learning Management System: emas2.ui.ac.id. Behavioural intention in the context of blended learning is crucial, as reflect students readiness as learners to use technology. Studying academic performance is vital in the higher education, as it serves as the primary indicator of the success of the learning process and the achievement of educational goals. Objective: The study was conducted to asses the academic performance of vocational students in the blended learning model. Methods: This study uses the concept of behaviour intention derived from the Technology Acceptance Model (TAM). This study uses a quantitative approach for the analysis, an online survey was conducted to obtain data from 65 respondents, who have taken information technology courses. The collected data is then processed using SPSS  using three stages: validity and reliability test, simple regression and moderation test. For the moderation test, subgroups based on gender and school origin were used. Findings: The result showed a significant effect behaviour intention on academic performance among vocational students. The moderation test revealed different results for the indicators: gender (male vs female) and school origin (public vs privat school). Significant result were found for the female and public school as moderation categories. Keywords: behavior intention, academic performance, blended learning, vocational.